2014
DOI: 10.1103/physreva.89.033833
|View full text |Cite
|
Sign up to set email alerts
|

Signature of superradiance from a nitrogen-gas plasma channel produced by strong-field ionization

Abstract: Recently, Yao et al. demonstrated the creation of coherent emissions in nitrogen gas with two-color (800 nm + 400 nm) ultrafast laser pulses [New J. Phys. 15, 023046 (2013)]. Based on this two-color scheme, here we report on systematic investigation of temporal characteristics of the coherent emission at)) by experimentally examining its evolution with the increase of the plasma channel induced by the intense 800 nm femtosecond laser pulses at a nitrogen gas pressure of ∼25 mbar. We reveal unexpected tempora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 41 publications
5
54
0
1
Order By: Relevance
“…One can see that the built‐up delay and the pulse duration are inversely proportional to the gas pressure p , while the peak power scales up quadratically with p . This confirms that the 391.4‐nm radiation is of the nature of superradiance …”
Section: Molecular Nitrogen Ion Lasingsupporting
confidence: 71%
“…One can see that the built‐up delay and the pulse duration are inversely proportional to the gas pressure p , while the peak power scales up quadratically with p . This confirms that the 391.4‐nm radiation is of the nature of superradiance …”
Section: Molecular Nitrogen Ion Lasingsupporting
confidence: 71%
“…[20,21]. The femtosecond laser beam (1 kHz, 800 nm, ~40 fs) produced by a commercial Ti:sapphire laser system (Legend Elite-Duo, Coherent, Inc) was divided into two arms.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that although the existence of population inversion has been confirmed with systematic experimental investigations, the mechanism behind the establishment of the inverted population within an ultra-short period of only ~100 fs is still under hot debate. In fact, several models have been proposed to understand the physics of such air laser, including stimulated emission based on seed amplification in a population inverted system, four-wave mixing, and seed-triggered superradiance [17][18][19][20]. Nevertheless, none of these models has been completely confirmed and widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was demonstrated that the signals of air lasers at 391 nm and 428 nm, which respectively correspond to the (0–0) and (0–1) vibrational transitions between the B 2 Σ u + and X 2 Σ g + states of N 2 + , showed different behaviors when the polarization of the pump laser evolves from linear to circular . In addition, under low pressures at tens of mbar, superradiance owing to the quantum coherence via cooperation of an ensemble of excited N 2 + molecules may dominate the forward emissions when the dephasing time is long enough .…”
Section: Remote Lasing Actions By Femtosecond Laser Pulsesmentioning
confidence: 99%